Optimizing Image Media on Mathematics Learning Outcomes for High Grade Students in Elementary Schools - Khuluq, Khairul; Sukartono, Sukartono; Veranita, Ayu; Ariyati, Iin (Buletin KKN Pendidikan, 2024)
Learning media has an influence on learning success. Suitable learning media must be adapted to the abilities and development of the students the teacher will teach, so teachers must adapt the learning media to the students' needs. The research objectives are: 1) to describe the planning for the application of image media to fifth grade students at SD Negeri 02 Gempolan in mathematics subjects; 2) describe the implementation of learning for class V students at SD Negeri 02 Gempolan using image media; 3) Describe the supporting and inhibiting factors for implementing image media in mathematics learning for fifth grade students at SD Negeri 02 Gempolan; 4) Describe a solution to overcome the factors inhibiting the application of image media to class V students at SD Negeri 02 Gempolan. SD Negeri 02 Gempolan, Kerjo conducted this research. The principal, teachers and fifth grade students were the subjects of this research. Interviews, observation and documentation are the methods used in data collection. This research uses a qualitative approach with phenomenological methods. Data validity is carried out using source triangulation techniques and technical triangulation techniques. The research results show that the use of image media is able to foster student enthusiasm in learning, so that image media that is managed optimally can improve mathematics learning outcomes.